Evaluasi Tujuan Pembelajaran dalam Rencana Pelaksanaan Pembelajaran (RPP): Implementasi Standar Proses pada Pembelajaran Sastra - U'um Qomariyah (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2020)
The preparation and development of the lesson plan is a hallmark of teacher professionalism. To support the learning process, teachers must arrange lesson plans according to standards. The preparation of the RPP standards must pay attention to the core components of the RPP, one of which consists of learning objectives. For this reason, an RPP evaluation is needed to determine the quality of the learning being done. Based on this, this article aims to evaluate the learning objectives in the CSP literary learning. The method used in this research is descriptive evaluative. Evaluation of learning objectives is based on the classification (grouping) of learning objectives into the learning domain, the suitability of the main steps (sequences) needed to achieve the objectives, and the completeness of the learning objectives component. The results show that the formulation of learning objectives in the three lesson plans analyzed did not fully meet the ideal learning objectives. The evaluation is expected to provide input and follow up efforts for improvement and decision making.